Analysis The Effect of Trading Volume Activity and External Factors to Composite Stock Price Index - Fajri, Mega Barokatul; Wihandaru, Wihandaru; Hakim, Adi Lukman (MEC-J (Management and Economics Journal), 2020)
This research as a purpose to analyze the effect of trading volume activity and external factors such as exchange rates, BI Rate to composite stock price index listed on the Indonesian Stock Exchange. The object of this research is on the Indonesia Stock Exchange and Bank Indonesia. In this study, the data used were time-series data and the sampling method used was purposive sampling. The method of analysis used in this study is multiple regression models. Based on the analysis that has been done, it is known that the trading volume activity and BI Rate has no effect on the composite stock price index, while the exchange rate has a negative effect on the composite stock price index.